2015
DOI: 10.1002/chem.201502161
|View full text |Cite
|
Sign up to set email alerts
|

Ansa‐Complexes of [Mn(η5‐C5H5)(η6‐C6H6)]: Preparation, Characterization, and Reactivity of [n]Manganoarenophanes (n=1, 2, 3)

Abstract: We report the synthesis of [n]manganoarenophanes (n=1, 2) featuring boron, silicon, germanium, and tin as ansa-bridging elements. Their preparation was achieved by salt-elimination reactions of the dilithiated precursor [Mn(η(5) -C5 H4 Li)(η(6) -C6 H5 Li)]⋅pmdta (pmdta=N,N,N',N',N''-pentamethyldiethylenetriamine) with corresponding element dichlorides. Besides characterization by multinuclear NMR spectroscopy and elemental analysis, the identity of two single-atom-bridged derivatives, [Mn(η(5) -C5 H4 )(η(6) -C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…First, we modified the nature of the transition metal and found that no change in the barrier is observed when using the group 8 [CpM II (PhI)] + analogues (M=Fe, Os) as catalysts. At variance, the barrier is significantly reduced for the cycloaddition mediated by the isoelectronic d 6 ‐neutral [CpMn I (PhI)] complex [33] cat1‐Mn (ΔΔE=1.5 kcal/mol with respect to cat1 ), whereas the activity of its heavier group 7 counterparts ( cat1‐Tc and cat1‐Re ) is comparatively lower. A similar reduction in the barrier is found for the isolectronic‐d 6 group 9 [CpM III (PhI)] 2+ complexes cat1‐Co (M=Co) and cat1‐Rh (M=Rh) [34] .…”
Section: Resultsmentioning
confidence: 99%
“…First, we modified the nature of the transition metal and found that no change in the barrier is observed when using the group 8 [CpM II (PhI)] + analogues (M=Fe, Os) as catalysts. At variance, the barrier is significantly reduced for the cycloaddition mediated by the isoelectronic d 6 ‐neutral [CpMn I (PhI)] complex [33] cat1‐Mn (ΔΔE=1.5 kcal/mol with respect to cat1 ), whereas the activity of its heavier group 7 counterparts ( cat1‐Tc and cat1‐Re ) is comparatively lower. A similar reduction in the barrier is found for the isolectronic‐d 6 group 9 [CpM III (PhI)] 2+ complexes cat1‐Co (M=Co) and cat1‐Rh (M=Rh) [34] .…”
Section: Resultsmentioning
confidence: 99%
“…1–4 There is a plethora of literature precedence for late transition metal ansa -complexes 5 including group 7 elements. 6 Ansa -rhenocene complexes with Re III were reported by Heinekey et al 7 and Conway and coworkers. 8 They reported the synthesis of C(CH 3 ) 2 and Si(CH 3 ) 2 bridged rhenocenes respectively.…”
Section: Introductionmentioning
confidence: 88%